PENINGKATAN HASIL BELAJAR PAI MELALUI MODEL PEMBELAJARANPROBLEM BASED LEARNING KELAS IV SDN 18 TARANTANG TUNGGANG - Elismawati (Adiba Aisha Amira, 2024)
This research was motivated by problems in Islamic Religious Education (PAI) learning in class IV of SDN 18 Tarantang Tunggang. Teachers still teach conventionally without utilizing technology, so that learning becomes monotonous. In addition, the enthusiasm, motivation to learn, and initiative to ask questions of students are still low, which causes less than optimal Islamic Religious Education learning outcomes. To overcome these problems, the Problem Based Learning (PBL) learning model was applied. This Classroom Action Research (CAR) was conducted in two cycles with 12 subjects of class IV students of SDN 18 Tarantang Tunggang in the 2024/2025 Academic Year. The indicator of success is if more than 75% of students get a score above or equal to the KKM (70). The results of the study showed that in cycle I, teacher activity reached 70%, student activity 75%, and learning outcome completion 63%. In cycle II, teacher activity increased to 100%, student activity 93%, and learning outcome completion reached 95%. Thus, the success indicator was achieved in cycle II, and the research was stopped. Conclusion: The implementation of the Problem Based Learning model has proven effective in improving the PAI learning outcomes of grade IV students of SDN 18 Tarantang Tunggang.